Cultural foundations of education - Pai, Young (Prentice Hall, 2006)
This thought-provoking book examines education as a cultural phenomenon and explores the implications of this perspective on schooling, multicultural education, educational development, and the process of teaching and learning. The authors combine the concepts of anthropology, education, schooling, teaching, and learning into an insightful introduction to the study of the cultural basis of education. Key topics include conflict between core and youth values, minority languages in the classroom, contemporary analysis of the IQ issues, recent school reform efforts, a new look at approaches to multicultural education, the postmodern conception of childhood and its educational implications, a discussion of performance assessment, communication and learning styles, and intercultural communication and competence. For teachers or any individuals interested in the relationship between social context and educational issues.